Scientific and technical assistance concerning the survival, establishment and spread of Batrachochytrium salamandrivorans (Bsal) in the EU. (28th February 2017) - ,; Balàž, Vojtech; Gortázar Schmidt, Christian; Murray, Kris; Carnesecchi, Edoardo; Garcia, Ana; Gervelmeyer, Andrea; Martino, Laura; Munoz Guajardo, Irene; Verdonck, Frank; Zancanaro, Gabriele; Fabris, Chiara
Abstract: A new fungus, Batrachochytrium salamandrivorans (Bsal), was identified in wild populations of salamanders in the Netherlands and Belgium, and in kept salamander populations in Germany and the United Kingdom. EFSA assessed the potential of Bsal to affect the health of wild and kept salamanders in the EU, the effectiveness and feasibility of a movement ban of traded salamanders, the validity, reliability and robustness of available diagnostic methods for Bsal detection, and possible alternative methods and feasible risk mitigation measures to ensure safe international and EU trade of salamanders and their products. Bsal was isolated and characterised in 2013 from a declining fire salamander ( Salamandra salamandra ) population in the Netherlands. Based on the available evidence, it is likely that Bsal is a sufficient cause for the death of S. salamandra both in the laboratory and in the wild. Despite small sample sizes, the available experimental evidence indicates that Bsal is associated with disease and death in individuals of 12 European and 3 Asian salamander species, and with high mortality rate outbreaks in kept salamanders. Bsal experimental infection was detected in individuals of at least one species pertaining to the families Salamandridae, Plethodontidae, Hynobiidae and Sirenidae. Movement bans constitute key risk mitigation measures to prevent pathogen spread into naïve areas and populations. The effectiveness of a movement ban is mainly dependent on the import volumes, possibility of Bsal to remain viable outside susceptible/tolerant species, and the capacity to limit illegal movements. Duplex real‐time PCR can be used to detect Bsal DNA, but has not been fully validated. Quarantining salamanders, enacting legislation that requires testing of animals to demonstrate freedom from Bsal, before movement can take place, restricting salamander movements, tracking all traded species, hygienic procedures/biosecurity measures before and during movements, and increasing public awareness are relevant measures for ensuring safe intra‐EU and international trade of salamanders.